Small cities development and internationalization during the rapid transformation period in China / Wang Qianyi - Wang, Qianyi (2018)
China’s economy has become famous for two reasons: one is the fast growth after the open-up reform with the double digit growth rate being recorded; the second is the use of globalization to drive its growth. As the growth model carrier, cities in China bear the responsibilities to drive the county economic development. The development of China’s cities reflects the coordination among local stakeholder in land management, spatial planning, economic development, institutional management and infrastructure allocation. The literature review illustrates the lack of researches towards the low-tier city development and internationalization in China. The lights have been shed to the major metropolises, such as, Beijing, Shanghai and so on. Those low-tier cities (in prefectural level and county level) received less concerns. However, even low in urban hierarchy, less in national support, and impossible to duplicate major cities’ growth mode, some of small cities in China obtain international reputation and shape their development mode with local characteristics. Therefore, the low tier cities, largest in number, devoting in national growth, deserve attention. By adopting the documentary review and case study approach, the thesis qualified the small city development and globalization process through the case study of Quanzhou, Yiwu and Nanning. The thesis findings inform the traditional development mode (such as, relying heavily on heavy investment, export-oriented economy) may not be easily duplicated. Leveraging on local advantages (such as, culture, kinship, and government support), the low-tier cities can gain their positions in the global arena. Further, city growth is not merely a reflection of growth theory, but an outcome involving the interaction of governments, spatial configurations, culture and historical legacy, and local stakeholders.